Roles and functions of code switching in the teaching of psychology at the University of Constantine - BENSAKESLI, Antar (Journal of Human Sciences, 2020)
The present research consists of analyzing code switching in the teaching of psychology at the University of Constantine. The aim is to discover qualitatively and quantitatively the didactic functions of this phenomenon and its implications in a context of teaching / learning of non-linguistic disciplines. We thus engaged in a sociolinguistic investigation by non-participant observations and audio recordings of the interactions in order to discover the use of the languages present, to determine the role and the implications of code switching in the course of the lessons. We have thus discovered that alternation relays or springboards occupy contradictory functions in psychology learners and teachers, thus suggesting a one-sided discourse of teachers, poor in interactivity, but rich in terminology of the specialty.